2015
DOI: 10.3892/ijo.2015.3311
|View full text |Cite
|
Sign up to set email alerts
|

ATP-site binding inhibitor effectively targets mTORC1 and mTORC2 complexes in glioblastoma

Abstract: Abstract. The PI3K-AKT-mTOR signaling axis is central to the transformed phenotype of glioblastoma (GBM) cells, due to frequent loss of tumor suppressor PTEN (phosphatase and tensin homolog deleted on chromosome 10). The mechanistic target of rapamycin (mTOR) kinase is present in two cellular multi-protein complexes, mTORC1 and mTORC2, which have distinct subunit composition, substrates and mechanisms of action. Targeting the mTOR protein is a promising strategy for GBM therapy. However, neither of these compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The effect of the mTOR inhibitor KU0063794 on Akt phosphorylation is expected and has been described before (34). In fact, Akt (Ser-473) is a known substrate of mTOR, and mTOR has been shown to regulate Akt phosphorylation at that site (35)(36)(37)(38).…”
Section: Spleen Tyrosine Kinase Blocks Autophagic Tau Degradationmentioning
confidence: 73%
“…The effect of the mTOR inhibitor KU0063794 on Akt phosphorylation is expected and has been described before (34). In fact, Akt (Ser-473) is a known substrate of mTOR, and mTOR has been shown to regulate Akt phosphorylation at that site (35)(36)(37)(38).…”
Section: Spleen Tyrosine Kinase Blocks Autophagic Tau Degradationmentioning
confidence: 73%
“…The second generation of inhibitors targets both TORC1 as well as TORC2 by competing with ATP at the catalytic site of the mTOR kinase, which is present in both complexes [202,203]. Similar to rapalogs, they can decrease protein translation and attenuate cell proliferation in several cancer cell lines [204,205].…”
Section: Pharmacological Use Of Different Mtor Inhibitor Familiesmentioning
confidence: 99%
“…Insulin could serve its roles though mTOR (28,29). Neil et al determined that insulin may induce activation of mTOR signaling in glioblastoma cells (41). Fritzen et al observed that mTOR signaling via unc-51 like autophagy activating kinase 1 may mediate the autophagy-inhibiting effect of insulin in human skeletal muscle (42).…”
Section: Discussionmentioning
confidence: 99%